2007
DOI: 10.1542/peds.2006-3260
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Infants as Young Adults: A Swedish National Cohort Study

Abstract: The majority of adults who were born very preterm lived an independent and self-supportive life. Moderately preterm birth carries a considerable risk for long-term impairment. There are strong economic incentives for secondary prevention of disability associated with preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
172
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(190 citation statements)
references
References 19 publications
12
172
2
4
Order By: Relevance
“…This finding is consistent with a large research literature showing that infants born prematurely have less favorable long-term educational and social outcomes (e.g., Moster et al 2008;Lindstrom et al 2007). Additionally, individuals with NS whose parents have higher education levels are at reduced risk for cognitive and adaptive difficulties (Pierpont et al 2010a;Pierpont et al 2009).…”
Section: Adaptive Behaviorsupporting
confidence: 90%
“…This finding is consistent with a large research literature showing that infants born prematurely have less favorable long-term educational and social outcomes (e.g., Moster et al 2008;Lindstrom et al 2007). Additionally, individuals with NS whose parents have higher education levels are at reduced risk for cognitive and adaptive difficulties (Pierpont et al 2010a;Pierpont et al 2009).…”
Section: Adaptive Behaviorsupporting
confidence: 90%
“…Of the few population-based studies, most are regional or rely on constrained national registry data. [41][42][43][44] The study that is most similar to ours is the Netherlands Project on Preterm and Small for Gestational Age Infants study in VLBW/VP infants born in 1983. 45,46 As in our study, Hille et al, 46 reporting from the POPS study cohort at age 19 years, found that VLBW survivors had greater difficulty establishing social contacts but did not have elevated risks of psychopathology compared with their term-born peers.…”
Section: Discussionmentioning
confidence: 66%
“…Preterm birth is associated with poorly understood impairments in cognitive and motor skills that last at least into adolescence and probably throughout life (Chyi, Lee, Hintz, Gould, & Sutcliffe, 2008;Lindstrom, Winbladh, Haglund, & Hjern, 2007;Morse, Zheng, Tang, & Roth, 2009). We used a cTBS protocol that induces an LTD-like plastic response to assess motor cortical plasticity in a group of adolescents born preterm (between 26 and 36 weeks gestational age).…”
Section: Assessment Of the Capacity For Plasticitymentioning
confidence: 99%